Performance task as instrument for evaluation among grade vi pupils in public elementary schools - Martin, Matronillo Del Mundo; Omela, Michel C. (Asian Journal of Assessment in Teaching and Learning, 2020)
This study aimed at determining the status of implementation and usefulness of Performance Task Evaluation (PTE) as an evaluation tool among Grade-VI pupils of Ramon District for the School Year 2018-2019. In this study, the implementation and usefulness of PTE were analyzed using quantitative research. In addition, related factors in implementing the evaluation model were determined. Then, based on the findings, programs and interventions were developed to improve the academic achievement of the Grade VI pupils through PTE. The respondents believed that PTE is being implemented in terms of practices. Therefore, the implementation of the PTE should be considered as a tool of evaluation. The respondents believed that PTE is useful in terms of academics, attitude and instructions. Pupils believed that PTE is useful in providing learning skills necessary for the education since PTE develops the skills of every pupil. Besides, through PTE pupil enhances their skills and potential using the updated and reliable assessment and evaluation tool.  The faculty and pupils should attend seminars that will gain knowledge for the implementation of PTE to easily develop a solution or action for its effective implementation. Besides, improved the monitoring system of the implementation of PTE through seminars, trainings, workshop and additional assessment examination. Moreover, the Department of Education Ramon District and recognized pupil government organizations may provide co-curricular activities that would allow maximum participation of the pupils to experience different challenges in education towards a better appreciation of their currently enrolled in elementary through PTE.